POSSIBLE CONFOUNDERS IN THE REPORTED ASSOCIATION BETWEEN AUTISM SPECTRUM DISORDER (ASD) AND EXPOSURE TO SELECTIVE SEROTONIN REUPTAKE INHIBITORS (SSRIS) DURING PREGNANCY. Issue 1 (14th December 2015) - Bruyne, Pauline De; Barzilay, Eran; Koren, Gideon
Abstract : Background: Autism has been in the forefront of public concern because of reported increase in prevalence and growing interest in the role of environmental risk factors in autism. A recent meta-analysis by Man et al. (2015) reported an increased risk of ASD in children of mothers exposed to SSRIs during pregnancy (adjusted OR 1.81, 95% CI 1.47–2.24). However, association may not imply a causal relation between SSRI exposure and ASD. We hypothesize that underlying disease might have confounded the published result. Materials and methods: A literature review was performed in order to identify possible confounders in the reported association. The list of search terms included but was not limited to following terms: 'Pregnancy', 'maternal', 'depression', 'child behaviour', 'health care seeking behaviour'. Results: Retrieved articles were classified in following four domains of possible confounders: 1/ direct link between depression and ASD, 2/effect of depression on interaction with the child, 3/effect of depression on other risk factors of ASD and 4/ascertainment bias. In the last domain, we examined the effect of depression on the way mothers perceive and report on the behaviour of their child and the effect of maternal depression on healthcare seeking behaviour. Analysis suggests that there are important merits to all those four domains. Conclusion: Because of obvious ethical reasons, research on exposure during pregnancy is mostly restricted to systematic review and meta-analysis of observational studies. Although this has resulted in a treasury of information, possible confounders must be taken into account when interpreting the results.